'Straight and Late': Analytical Perspectives on Coltrane's Time-feel. (2nd January 2020) - Mermikides, Milton
ABSTRACT: This paper examines aspects of Coltrane's rhythm by adopting a relatively simple model of expressive micro-timing ("time-feel"), wherein swing (the symmetry of the offbeat subdivision) is treated as a discrete parameter for each ensemble member and is kept distinct from latency – the relative micro-rhythmic placement of each player's onbeats. The interaction of these two parameters is examined in the context of original analyses from Coltrane's repertoire, with the micro-rhythmic placements of onsets in Coltrane's ensemble visualized in linear, planar and – similar to those conceived by Charles Mingus 1 and employed analytically by Fernando Benadon 2  – circular representations at the tactus level. Coltrane's characteristically straight-and-late eighth feel 3 is here seen not just as a solution to creating a swung offbeat at high tempos, but as a dynamic expressive mechanism, with the ability to move from a high swing value to a behind-the-beat straight feel in varying consonance and friction with his ensemble's onbeat and offbeat placement. This perspective offers novel analytical and pedagogical approaches, as well as an insight into an otherwise hidden facet of Coltrane's virtuosity.